1998
DOI: 10.1007/s003450050085
|View full text |Cite
|
Sign up to set email alerts
|

The prostate anesthetic block for outpatient prostate surgery

Abstract: With the emergence of minimally invasive techniques for the treatment of benign prostate hyperplasia and the need to reduce health care costs, a simple and effective prostate anesthetic block may allow more procedures to be done in an outpatient or office setting. As based on neuroanatomy studies of the prostate, the perineal approach appeared to be the best way to anesthetize the prostate. This technique was used in 43 patients who underwent interstitial laser coagulation an outpatient or office setting. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 11 publications
0
6
0
2
Order By: Relevance
“…The nerve fibers course along the branches of the inferior vesical artery and dorsal vein of the penis to form bilateral neurovascular bundles and are the main sensory supply of the prostate (52, 53). These bundles straddle the posterolateral aspect of the prostate at 5 and 7 o'clock positions, in the angle formed by the seminal vesicle with the base of prostate (54). The branches decussate extensively and ramify between the capsule and the Denonvilliers' fascia (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The nerve fibers course along the branches of the inferior vesical artery and dorsal vein of the penis to form bilateral neurovascular bundles and are the main sensory supply of the prostate (52, 53). These bundles straddle the posterolateral aspect of the prostate at 5 and 7 o'clock positions, in the angle formed by the seminal vesicle with the base of prostate (54). The branches decussate extensively and ramify between the capsule and the Denonvilliers' fascia (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In some aspects ILC seems to offer an advantage over TURP; blood loss is minimal and the risk of TUR syndrome is eliminated, as saline rather than glycine is used as the irrigant. Furthermore, the possibility of administering ILC under local anaesthesia is an attractive option because patients undergoing surgery for BPH are elderly and often have significant comorbidity [8,9]. However, direct comparisons of ILC and TURP in randomized trials are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In 1984, Orandi emphasized the importance of using local anesthesia for urological endoscopic surgeries such as transurethral incision and resection of the prostate, visual urethrotomy, ureteral meatotomy, and resection of primary and recurrent bladder tumors [8] . In a similar study, Issa et al [13] performed transperineal prostatic block in 43 patients who underwent interstitial laser coagulation of the prostate in either an outpatient or office setting. These authors confirmed that the majority of their patients tolerated the procedure, concluding that perineal prostatic block is a safe, economical, and effective anesthesia technique for minimally invasive prostate surgeries.…”
Section: Discussionmentioning
confidence: 99%